PEMBAHARUAN PENDIDIKAN TINGGI HUKUM DI INDONESIA - Fadjar, A. Mukthie (Jurnal Bestari, 1992)
"The educatio of law does not produce skillful lawyer," said Ismail Saleh, the minister of law. Is it denoting that everything is dull in its curiculum? The dawndall of education in the developing countries actuallly must be understood in relation with the useless of law itself. This phenomena can be solved by engineering law tradition. You can observe, for instance, law curriculum engineering below.